2019
DOI: 10.3390/s19214818
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Encoder-Decoder Structured FCN Based LiDAR to Color Image Generation

Abstract: In this paper, we propose a method of generating a color image from light detection and ranging (LiDAR) 3D reflection intensity. The proposed method is composed of two steps: projection of LiDAR 3D reflection intensity into 2D intensity, and color image generation from the projected intensity by using a fully convolutional network (FCN). The color image should be generated from a very sparse projected intensity image. For this reason, the FCN is designed to have an asymmetric network structure, i.e., the layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 29 publications
0
35
1
Order By: Relevance
“…Interestingly, it has been reported that the deep learning-based encoder-decoder structured fully convolution network (ED-FCN) can successfully generate camera-captured-like color images from heterogeneous LiDAR reflection data [ 19 , 20 , 21 ]. Note that the ED-FCN network is originally applied for semantic segmentation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, it has been reported that the deep learning-based encoder-decoder structured fully convolution network (ED-FCN) can successfully generate camera-captured-like color images from heterogeneous LiDAR reflection data [ 19 , 20 , 21 ]. Note that the ED-FCN network is originally applied for semantic segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the ED-FCN network is originally applied for semantic segmentation. The methods [ 19 , 20 , 21 ] consist of two steps, as shown in Figure 1 . In the first step, LiDAR 3D reflection data are projected into 2D color image coordinate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations